Derangements of tonicity and implications for veterinary patients - Reinhart, Jennifer M. (Kansas State University, 2014)
Tonicity is property of a solution that is defined as the total effective (impermeable) osmole concentration that drives fluid movement across a semipermeable membrane via osmosis. Tonicity is related to but distinct from solution osmolality, which is a summation of all solute concentrations, regardless of the solute membrane permeability. In the mammalian body, tonicity is tightly regulated at both a cellular and systemic level; tonic derangements cause rapid change in cell and tissue volume leading to significant dysfunction. Input from the central nervous, circulatory, endocrine, gastrointestinal, and urinary systems are integral to osmoregulation, so many diseases in veterinary medicine are associated with tonicity disorders. However, because the homeostatic mechanisms that control tonicity overlap with those regulating electrolyte and acid-base balance as well as hydration and vascular volume, tonic consequences of disease can be difficult to isolate. Understanding of disease-associated changes in tonicity is further complicated by the fact that the tonic contributions of many solutes that accumulate in disease are unknown. Additionally, direct assessment of tonicity is difficult because tonicity is not just a physiochemical property, but it implies a physiologic effect. Thus, simple summation of osmole concentrations is an inadequate measurement of tonicity. The following report includes three studies investigating various aspects of tonicity as it applies to veterinary patients. Chapter 2 reports a study that examines the tonic effects of ketoacids and lactate using two different in vitro red blood cell assays. Results demonstrated that the ketoacids, beta-hydroxybutyrate and acetoacetate, behave as ineffective osmoles while the tonic behavior of lactate is variable, implying a more complex cellular handling of this anion. Two additional studies examine whether the mean corpuscular volume difference (dMCV) is a novel clinical marker for hypertonicity in dogs. Results of separate retrospective (Chapter 3) and prospective (Chapter 4) studies provide evidence that dMCV is a useful clinical marker for hypertonicity in dogs.
Keywords: Osmolality; Red blood cells; Sodium; Diabetes mellitus; Dog; Metabolism; Health Education (0680); Health Sciences (0566); Physiology (0719); Veterinary Medicine (0778)